Peranan (Tokopedia) Sebagai Mediapromosi dalam Meningkatkan Minat Beli Konsumen Ikan Hias Air Laut di PT Indotama Putra Wahana Bekasi, Jawa Barat - Sumarni, Sumarni; Sulkifli , Sulkifli; Ridwan, Ridwan (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to determine the role of Tokopedia as a promotional media in increasing consumer purchase interest of saltwater ornamental fish at PT Indotama Putra Wahana, Bekasi. The background of this study is the rapid development of information technology which also influences marketing strategies, including through e-commerce platforms such as Tokopedia. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation of consumers and the company. The results of the study indicate that promotional features available on Tokopedia such as TopAds, shop vouchers, cashback, and broadcast chat play an important role in increasing product visibility and encouraging consumer purchases. In addition, product reviews and ratings from previous buyers are also determining factors in making purchasing decisions.